Coordinated fault tolerant control of over-actuated electric vehicles based on optimal tyre force distribution. (2017) - Luo, Yugong; Cao, Kun; Xie, Laiqing; Li, Keqiang
Actuator faults of the driving/steering/suspension subsystems may lead to instability in over-actuated electric vehicles. Though many fault tolerant control methods that rely on partial subsystems exist, a novel coordinated fault tolerant control (CFTC) method based on optimal longitudinal/lateral/vertical tyre force distribution is proposed. First, the coordination principle of all the actuator subsystems is explained using vehicle dynamics control equations. Then, an optimal longitudinal/lateral/vertical tyre force distribution method is established. Results of simulations and hardware-in-the-loop (HIL) experiments show that the CFTC method successfully coordinates all the subsystems to compensate actuator faults and effectively improve vehicle stability and safety.